Human Resource Management in Quality Improvement of ZIS Management at LAZISMU Purbalingga in the New Normal Era - Hanif Ardiansyah (Profesional Muda Cendekia Publishing, 2021)
The purpose of this research is to analyze human resource management in improving the quality of zakat, infaq, and shodaqoh (ZIS) management at LAZISMU Purbalingga. This research is qualitative non-experimental (descriptive) research and uses phenometric approach. This research was executed at the Lembaga Amil Zakat Infak Shodaqoh Muhammadiyah (LAZISMU) Purbalingga, Central Java. The source of this research is the director of LAZISMU, The Employees, and some people who paid the ZIS at LAZISMU Purbalingga. Researchers act as instruments as well as data collectors. Other instruments are also used to support in completing data research. In this study, researchers used interview, observation and documentation methods. Data analysis techniques using qualitative descriptive analysis. The data analysis technique is divided into several steps including data collection, data presentation and conclusion drawing. The results showed there are two types of employees at LAZISMU Purbalingga. First the employee or permanent employee, the second is the voluntary employee. The process of human resource management there are several stages, starting from the process of Recruitment, Placement, Coaching and Training, and Human Resources Evaluation. There is a uniqueness of the stages of human resources management compared to organizations and companies in general. ZIS management at LAZISMU Purbalingga is applied into various fields of activities. First the areas of education, economics, health, social and da'wah, and teh last is construction branch. Each areas has its own advantages and is certainly applied in activities that have many benefit for people.